Rola ośrodków wsparcia dziennego we wspomaganiu funkcjonowania rodziny z dorosłym dzieckiem z niepełnosprawnością intelektualną i/lub psychiczną - Szalast, Anna (Karkonoska Państwowa Szkoła Wyższa, 2012)
The overall perception of adults with intellectual and/or physical disabilities renders it necessary to consider them as individuals as well as in relation to their families, which are to be understood as natural links to communities. The exceptional situation of the families with intellectually and/or physically disabled children older than school age demands understanding and professional help. Day support centres, which constitute a major influence on the disabled, as well as their immediate environment, are an attempt at addressing these needs. The centres also allow for the achievement of a goal – they provide the families of adult children with intellectual and/or physical disabilities with support in its numerousaspects.
Keywords: rodzina; dorosłość; niepełnosprawność intelektualna; środowiskowy dom samopomocy